Harms – Gogol – Dostoevsky (“Old Women” – “Vij” – “Crime and Punishment”) - Shults, Sergey (Slavica, 2018)
In terms of historical poetics and intertextuality, parallels are drawn between "Old Woman" by D. Harms, "Vij" by N. Gogol and "Crime and Punishment" by F. Dostoevsky. As far as the three authors are concerned, their common features are revealed, together with the transformation of the motives of the ugly infernal old woman, which are depicted in the context of mythopoetics, historiosophy and social history by the three authors. Concerning the texts produced by their followers the term “post-text” is introduced, which is meant to include the dialogical connotations of literary evolution. The role of “vertex composition” (a term coined by V.M. Zhirmunsky) in works of Modernism/ Avant-garde is also touched upon.